2022
DOI: 10.56825/bufbu.2022.4123012
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic effects of ketamine-guaifenesin and isoflurane anesthesia for diaphragmatic herniorrhaphy in buffaloes

Abstract: The study was undertaken on twelve buffaloes weighing 313 to 442 kg and age between 4 to 9 years to evaluate double drip of ketamine-guaifenesin and isoflurane anaesthesia for diaphragmatic herniorrhaphy. In Group I and II animals, anesthesia was induced with double drip of ketamine-guaifenesin (1000 mg of ketamine, 25 gm of guaifenesin in 500 ml Dextrose 5% solution) 1.5 ml/kg body weight. Double drip 2.5 mL/kg/h in Group I and 2 % isoflurane in Group II was used for maintenance of anaesthesia. In both the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Farrow (1999) outlined that radiographic methods can easily confirm the existence of one or more reticular abnormal cells, but it is not always clear whether a specific reticular object is to blame for an animal’s symptoms. Reticular magnets are used to attempt to prevent foreign body damage by drawing potentially dangerous wire or nails to the magnet’s surface and retaining them there, preventing reticulum puncture (Ghanshyam et al , 2020). Talekar et al (2018) reported a study on 06 animals (04 Jaffarabadi buffaloes and 02 Gir cows) with DH.…”
Section: Introductionmentioning
confidence: 99%
“…Farrow (1999) outlined that radiographic methods can easily confirm the existence of one or more reticular abnormal cells, but it is not always clear whether a specific reticular object is to blame for an animal’s symptoms. Reticular magnets are used to attempt to prevent foreign body damage by drawing potentially dangerous wire or nails to the magnet’s surface and retaining them there, preventing reticulum puncture (Ghanshyam et al , 2020). Talekar et al (2018) reported a study on 06 animals (04 Jaffarabadi buffaloes and 02 Gir cows) with DH.…”
Section: Introductionmentioning
confidence: 99%